Infrared thermography detects soccer-induced residual fatigue: a single-case study - da Silva, Alisson G. (2022)
We analysed the effect of different volumes of a soccer simulation protocol (SSP) on skin temperature (Tsk), muscle damage, and inflammation to investigate whether thermography can detect residual fatigue. We conducted this single-case study with a 17-year-old soccer player in a military boarding school. The participant performed an SSP twice with different duration (45 min and 90 min). At 24 h pre, 24 h post, and 48 h post each condition, thermograms were taken to measure Tsk overlying quadriceps, hip adductors, hamstrings, and gastrocnemius. Also, blood samples were obtained to quantify both creatine kinase (CK) and C-Reactive Protein (CRP) concentrations. Following the 90-min SSP, Tsk increased during the recovery period in all analysed regions; CK peaked after 24 h (336 U·L-1) with values 273.3% higher than baseline (90 U·L-1), remaining elevated 48 h post-match (185.6%) (257 U·L-1); CRP increased 182.5% after 24 h (1.13 mg·L-1) when compared to baseline (0.40 mg·L-1) and peaked at 48 h post (432.5%) (2.13 mg·L-1). However, following the 45-min SSP, there was no increase in Tsk, CRP, and the CK values did not indicate muscle damage. Thermography is capable of detecting soccer-induced residual fatigue in a young military player. Monitoring Tsk changes via thermography can be a promising non-invasive approach to monitoring muscle recovery status.